A Nexus between Identity Awareness and Decolonization Process of Local Economy: Indonesian Experience - Muhammad Hanif Al-hakim (AL- IKTISAB Journal of Islamic Economic Law, 2017)
This paper will examine four significant economic events – namely, Indonesiangovernment’s measure to nationalize the existing foreign enterprises in 1950s; debatein between 1949-1957 in searching of an appropriate ideology to be adopted as frameworkin devising economic policies; the rise of Sharia-compliant bank in early 1990s; and theemergence of Islamic co-operative financial institution called Bay al-Mâl wa al-Tamwîl(BMT), in relation to the advancement of people awareness of their right identity. Thefinding says that reality stated that decolonization movement in Indonesia from bottomupthat is contrary from ideal studies, and it is always connected with real identity thatthe decolonized people are certain with. By then, identity awarness is the way to thedecolonisation process that will impact to Islamization of economics in Indonesia.